Investigation of Sintering Kinetics of Magnetite pellets during Induration - Kumar, TK Sandeep (Luleå tekniska universitet, Mineralteknik och metallurgi, 2015)
One of the measures of development and economy of a nation is its per capita consumption of steel, and the demand is fulfilled by iron ore. In the context of increasing environmental constraints and ores becoming leaner and leaner, recycling and utilization of ore fines becomes necessary. Pelletization, being one of the major agglomeration techniques is increasingly practiced across the world to produce agglomerates that can be fed into the metallurgical furnaces (say blast furnaces) for subsequent processing. In Europe, Sweden has the richest iron ore deposits, and mining and metals production contributes majorly to its net export. LKAB operates with magnetite ore bodies in the northern Sweden to produce magnetite pellets (26 MTPA) exports about 70 % of its product to the European Steel producers. Therefore, constant efforts are necessary to maintain and improve the quality of magnetite pellets, and it is necessary to enhance the understanding on the reaction kinetics and mechanisms responsible while producing pellets.Magnetite pellets prepared from the fines are indurated (heat hardened) to attain the quality standards in terms of strength and other metallurgical properties. The quality of magnetite pellet is primarily determined by the physico-chemical changes the pellet undergoes as it makes excursion through the gaseous and thermal environment in the induration furnace. Among these physico-chemical processes, the oxidation of magnetite phase and the sintering of oxidized magnetite (hematite) and magnetite (non-oxidized) phases are vital. Rates of these processes not only depend on the thermal and gaseous environment the pellet gets exposed in the induration reactor but are also interdependent on each other. Therefore, a doctorate project is undertaken to systematically understand these processes in isolation to the extent possible and quantify them seeking the physics. With this motivation, the current study is focused on investigating the sintering phenomena involved during induration of magnetite ...